"Nós somos ciganos. E você, o que é?": processos identitários entre três gerações de ciganos calon no Estado do Espírito Santo - Cardoso, Grecy Kelle de Andrade (2018)
Gypsies (or Roma people) have a long diaspora in different territories and nationalities. Although differences were found in some gypsy groups, characteristics such as gender relations, the valorization of socialization that occurs in the group context, and learning of laws and traditions have been considered relevant in the construction of gypsies’ identities. Grounded on the Theory of Social Identity, the present study aims to analyze the identity processes and the context of ethnic socialization between three generations of Calon gypsies, in a gypsy camp in the State of Espírito Santo (Brazil). For that purpose, two complementary studies were carried out: a study, through an ethnographic approach, through information annotated in field journals (Study 1); and an intergenerational study, performed through interviews with semi-directed interview script focusing on three generations, the elderly, adults and children. Nineteen members of the gypsy group participated in the study, with ages ranging from 48 to 95 (first generation), 24 and 41 (second generation) and 04 and 12 (third generation). The data treatment was constructed from a content analysis and a lexical analysis by the Descending Hierarchical Classification. The main results demonstrated are: (i) in the first generation, the “old trunks” (seniors) emphasize the characteristics about the past, nomadism of the “time of mule troops” and other characteristics of their ancestors; (ii) in the second generation, the “Calon men” highlight gypsianism based on cultural elements, such as comparing gypsies and non-gypsies and the different generations of the group; and the women (gadjés) report their insertion in gypsy life and the identity dilemmas arising from this dual social insertion; and (iii) in the third generation, the Calin children report information related to gypsy childhood, to experiences of insertion into the school environment and to opportunities for future life, with particular emphasis on housing, marriage and expected social roles. Through a psychosocial analysis about the investigated phenomena, we understand the gypsy identity, as observed in the group. It is an identity expression, constructed in the context of ethnic socialization, which is materialized as being gypsy, also due to generational and gender hierarchies. This expression has been maintained with strong connotation of value and positive affect. We hope that the present research will help to increase knowledge about the gypsies, due to need of resignifying the gypsies’ image in the social sense and the emergence of the gypsy question as a social question, legitimizing their demands in relation to their ethnic cultural specificities and needs.